A RISK MANAGEMENT DESIGN FOR THE PROJECT OF SURFACE TREATMENT PRODUCTION LINE AUTOMATION AT PT DIRGANTARA INDONESIA - Ferro Fathurahman, Aryo
PT Dirgantara Indonesia is a State-Owned Enterprise or BUMN engaged in the aviation industry with various services for aircraft production and maintenance. The actual condition experienced by the company is that there are still many production lines that are done manually by relying on human labor and expertise, one of which is the surface treatment production line. This causes problems, namely the acquisition of Key Performance Indicators (KPI) for the Surface Treatment area which is often not fulfilled, on the other hand, the standards and requirements desired by customers are also increasing. Therefore, PT Dirgantara Indonesia, especially in the manufacturing engineering division, plans a Surface Treatment Automation project. To increase success and minimize disruption to the project, the project team prepares a risk management study. This study aims to design project risk management by identifying, evaluating and designing risk response proposals. The risk management plan is based on the PMBoK framework with several additional methods. Mapping of business processes and risks is carried out using a Work Breakdown Structure and a Risk Breakdown Structure which is then synthesized into a Risk Breakdown Matrix. Risk assessment and analysis is carried out quantitatively using a probability/consequences matrix which then used as the basis for proposing forms of risk treatment for high priority risks. This research resulted in a risk management design that identified 44 risks in the project. The project risk consists of 10 high risk, 30 medium risk and 4 low risk. Risk with critical grouping is a prioritized risk for the proposed risk response design. The study produced 10 risk response proposals for critical risks with choices between avoid, mitigate, transfer and accept.